Migration networks and the Moroccan tourism: A panel data analysis - Samir Djelti; Mohamed Hadj Ahmed; Mohamed Seghir Guellil (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
This contribution aims to study the migration and tourism nexus. In the developed countries, the effect of migration on tourism has been widely analyzed. For the developing countries, this topic is more interesting because of the role that diaspora plays in fostering tourism to the home countries. Based on the theoretical and empirical literature, the effect of migration networks on tourism will be tested. On the one hand, global migration networks can have a positive effect on tourism through the increase of borders permeability in the osmosis theory logic. On the other hand, at the micro level, migrant generations, transactions, preferences, and emigrants' life style can adapt, promote, and advertise tourism of the home countries. To estimate the global effect of networks on Moroccan inflows of tourists from the eight OECD principal immigration countries, the gravity model has been used. The analysed data considers the statistics of the nine countries during nine periods. The results show a significant correlation between Moroccan tourism inward tourism and emigration, in addition to the exogenous variables, either in the Fixed Effects Model or in Dynamic panel one using GMM method. The results indicate also a concordance of the two models results, the fact that strengthen their role as robust tools for exploring the migration and tourism nexus. The statistical results confirm the positive effects of migration networks on the Moroccan tourism.
Keywords: F22; L84; 330; migration; networks; tourism; Morocco